Synthesis of 13C‐labeled parabens from isotopically enriched phenols using the Houben–Hoesch reaction. (26th July 2022) - Reber, Keith P.; Sivey, John D.; Vollmuth, Matthew; Gujarati, Priyansh D.
Abstract : Parabens are antimicrobial additives found in a wide array of consumer products. However, the halogenated compounds formed from parabens during wastewater disinfection are a potential environmental concern. In order to identify these transformation products and investigate their mechanism of formation, a synthetic route to ethyl parabens labeled with the stable isotope carbon‐13 at specific positions within the benzene ring was developed. This efficient two‐step procedure starts from commercially available 13 C‐labeled phenols and involves (1) initial acylation of the phenol via a Houben–Hoesch reaction with trichloroacetonitrile followed by (2) a modified haloform reaction of the resulting trichloromethyl ketone to afford the corresponding 13 C‐labeled ethyl parabens in 65%–80% overall yield. The scope of the modified haloform reaction was also investigated, allowing for the synthesis of other parabens derived from primary or secondary alcohols, including 13 C‐ and deuterium‐labeled esters. In addition, 4‐hydroxybenzoic acid can be formed directly from the common trichloromethyl ketone intermediate upon treatment with lithium hydroxide. This protocol complements existing methods for preparing 13 C‐labeled paraben derivatives and offers the specific advantages of exhibiting complete regioselectivity in the Houben–Hoesch reaction (to form the para ‐disubstituted product) and avoiding the need for protecting groups in the modified haloform reaction that forms the paraben esters. Abstract : 13 C‐labeled parabens were prepared from isotopically enriched phenols in two steps using a Houben–Hoesch acylation followed by a modified haloform reaction.